O "alvoroço do mangangá" : uma análise do processo patrimonialista do jongo na comunidade de São Mateus, Anchieta (ES) - Silva, Larissa de Albuquerque (2016)
This research aims to describe the processes of constitution and social and political organization of the community of São Mateus, black community located in the municipality of Anchieta"s (ES) rural area. It will be observed that their cultural practices, such as Jongo, are discursive elements, legitimating and demarcating the ethnic identity of the group with local players in setting up access to Public Policies. The social memory is addressed in this ethnography as an articulator element in the construction of the individual"s discourses, whose content is to valorize the past and their recreations and reinterpretations of the present. This fact occurs with jongo practitioners in the Espírito Santo, since, over the current legal situation by Articles 215 and 216 of the Federal Constitution of 1988 Brazil, the patrimonial policies of cultural practices were fomented by the State. Through ethnographic work, the research focuses on the symbolic dimensions of individuals" social actions, in order to understand how the different forms of mediation are responsible for weaving spaces of representation in social struggles around the São Mateus" Jongo.